Jet engine design - Lim, See Hong. (2011)
Jet engines have a wide range of applications in the modern aviation industry. They are used to power aircraft, cruise missiles and unmanned aerial vehicles. They can be modified for civil applications such as generators or engines as the design involves the same principles. These principles include thermodynamics, mechanics of materials and fluid dynamics. However, many people do not know how these jet engines work as it is a very specialized subject. The purpose of this project is to design a course material to teach non- mechanical engineers the process of designing a jet engine, through specially selected topics that are relevant to jet engine design, followed by a design exercise to consolidate what has been read earlier. Firstly, basic principles in thermodynamics are reviewed. These include the first and second laws, T-S diagram and the Brayton cycle. This will then be followed by a look at fluid dynamics where the properties of the flow of air are closer examined. The topics will end with a study of the mechanics of materials, where properties of the materials of the blades in the turbine and compressor, are studied. The design exercise will begin with analysis of the flow through a turbofan and the components. Blade and disc stresses are calculated next to find out how much stress they are undergoing when in operation. With this information completed, the design process is completed.